2011
DOI: 10.5114/wiitm.2011.20993
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of minimally invasive surgery in the Czech Republic

et al.

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…[2] Because of faster postoperative recovery and reduced postoperative complications, laparoscopic appendectomy is now being more and more widely used for treating acute appendicitis. [14], [15], [16], [17], [18] The key technical aspect in laparoscopic appendectomy is the treatment of appendix stump closure. Nowadays, stapling and endoloop techniques are the most popular ones in securing the appendix stump.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Because of faster postoperative recovery and reduced postoperative complications, laparoscopic appendectomy is now being more and more widely used for treating acute appendicitis. [14], [15], [16], [17], [18] The key technical aspect in laparoscopic appendectomy is the treatment of appendix stump closure. Nowadays, stapling and endoloop techniques are the most popular ones in securing the appendix stump.…”
Section: Discussionmentioning
confidence: 99%
“…According to mandatory European interdisciplinary recommendations for the surgical treatment of obesity, bariatric surgical interventions that limit food consumption by gastric capacity reduction (restrictive methods) include: vertical banded gastroplasty (VBG), laparoscopic sleeve gastrectomy (LSG), adjustable gastric bandage (AGB), and gastric bypass (GBP). A laparoscopic approach is considered the first choice among bariatric interventions [14], as is the case in other difficult gastric surgeries [16]. In connection with QOL, Stefaniak [17] found that patients had a more positive self-perception and body image following laparoscopic surgery than after conventional surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of laparoscopic colorectal operations is still increasing worldwide [11, 12], including among complicated surgical procedures [13]. As the demand for laparoscopic colorectal surgery increases, interest in the risk of conversion to open surgery grows as well.…”
Section: Discussionmentioning
confidence: 99%